Validity of the Digital Module Exploration of Physics Concepts in Making “Jember Batik Crafts” as an Effort to Support Local Wisdom-Based Multicultural Education - Lailatul Nuraini; Singgih Bektiarso; Safina Aulia Sani; Rike Dwi Wulandari (IKIP Mataram, 2023)
The prospective physics teachers was very important to be provided with an understanding regarding the local potential of an area that is integrated into the physics learning process as a strengthening of multicultural education. The use of digital modules in physics learning contains the concept of local Jember wisdom, namely making Jember batik crafts that have never been developed before. This research aimed to examine the validity of digital physics modules containing local wisdom